Problem Penegakkan Diagnostik Pasien dengan Massa di Paru: [Diagnostic Problems in Lung Mass Management] - Laksmi Wulandari; Nikson Eduard Faot (Faculty of Medicine Universitas Airlangga, 2017)
Background: Lung cancer are divided into 2 groups; i.e. Small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). About 30% of NSCLC is squamus cell carcinoma and the other is adeno carcinoma. Late diagnosis makes such a high mortality rate. Early diagnosis plays a very important role in the management of therapy. Case: Patients complain of chronic cough more than 6 months, decreased appetite and weight loss. Chest X-ray and CT scan show a density of round shape mass, with firm border and smooth regular edge, also lympnodes enlargement (T2N2Mx) stage IIb. Appearance of lung mass is benign according to clinically and radiologically. FNAB-CT Guiding results are difference each time examination. The first result is squamous cell carcinoma but the last result is teratoma. Discussion: Based on the multidisciplinary discussion on Tumor Board Meeting, the diagnosis was decide as Squamous cell Carcinoma. The choice management of stage IIb lung cancer is surgery (Lobectomy). Histopathology finding post surgery is a Squamus Cell Carcinoma. Patients were then given adjuvant chemotherapy for 4 cycles with Platinum Base regimen paxuscarboplatin with the aim of clearing micrometastase that may still be left behind. The complete respons of platinum based chemotherapy following surgery in early stage of squamous cell carcinoma. Conclusion: Difficulties of lung cancer diagnostic are still the problem in the management of lung mass. Difference of diagnostic makes difference treatment choice. Multidiscipline discussion is needed to decide the diagnostic and treatment judgment.